Static MRI for diagnosis of bulbous urethral strictures and assessment of spongiofibrosis grade - A. B. Bogdanov; M. I. Katibov; E. I. Veliev; D. M. Monakov; D. A. Goncharuk; G. I. Akhverdieva; A. S. Polyakova; V. A. Vardanyan (Вестник урологии, 2023)
Introduction. Insufficient sensitivity and specificity of existing methods for diagnosing urethral stricture require more accurate methods, which may include magnetic resonance imaging (MRI).Objective. To study the possibilities of MRI to assess the extent of bulbous urethral stricture and spongiofibrosis grade.Materials & methods. The study included six men with bulbous urethral stricture, who underwent non-transecting anastomotic urethroplasty via ventral approach. Before surgery, all patients underwent retrograde urethrography according to the standard method and urethral MRI according to their own method, and their data were compared with intraoperative parameters.Results. The length of the stricture according to retrograde urethrography averaged 11.5 ± 6.3 mm, MRI — 17.8 ± 10.9 mm, intraoperative measurement — 16.7 ± 9.1 mm. There was a significant difference between the mean length of the stricture according to retrograde urethrography and the mean length according to intraoperative data (p = 0.028). There was no significant difference between the mean stricture length according to MRI data and the mean stricture length according to intraoperative data (p = 0.085). The length of spongiofibrosis according to MRI was 15.8 ± 13.6 mm on average, and 16.7 ± 12.9 mm according to intraoperative measurements. There was no significant difference between the average length of spongiofibrosis according to MRI and the average length according to intraoperative data (p = 0.092).Conclusions. MRI provides information comparable to intraoperative data on the extent of urethral stricture, location, and spongiofibrosis grade.